Keadilan dalam Layanan Kesehatan: Tinjauan Teoritis dan Praktis dari Perspektif Hukum - Suriyani Mansyur; Anindya Putri Permatasari; Amelia Agustina; Ahmad Ma’mun Fikri (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the concept of justice in healthcare services from a legal perspective, both normatively and practically, with a focus on the implementation of the National Health Insurance (JKN) program and the involvement of private hospitals as partners of BPJS Kesehatan. The study uses a normative approach with a case study. The findings show that although existing regulations contain the principles of justice and the right to health services, in practice there are still disparities in treatment between JKN and non-JKN patients, as well as weak legal protection for partner hospitals. This indicates a legal imbalance among the state, healthcare providers, and insurance participants. Therefore, policy reform is needed to affirm justice not only for patients but also for healthcare providers.